Reversible Growth Failure Among Hispanic Children: Instances of Psychosocial Short Stature - Nieves-Rivera, Francisco; González-De Pijem, Lilliam; Mirabal, Brenda (Puerto Rico Health Sciences Journal, 2014)
see manuscript